Physical Connectivity as Enabler of Unexpected Encounters With Information in Campus Development: A Case Study of South China University of Technology - Liu, Yubo; Ji, Mian; Deng, Qiaoming; Hu, Kai (Frontiers in Psychology, 2021)
This paper is an attempt to advance research on spatial potential for interdisciplinary innovation in university campuses by proposing a spatial quantitative method for innovation-driven renovation. The aim is to make use of the campus renovation to adapt to the new pedagogical structure of encouraging interdisciplinary innovation in the era of knowledge society. For this purpose, literature from management, psychology, and architecture are reviewed to provide insight into the relationship between innovation and physical environment. The existing research mainly focused on the characteristics of physical environment that supported individual innovative thinking or innovative interaction between people in building scale, which is relatively limited in this study for the campus scale since people are less likely to exchange academic information with strangers because of a lack of knowledge about their professional background. In this context, this research enriches the understanding of spatial potential for innovation by proposing a more effective way of increasing unexpected encounters with information, which are probably occurred while people passing by laboratories, seminars, or exhibitions of other disciplines. In this process, the unexpected encounters with information act as the medium or promotion factor for face-to-face interaction. This kind of innovative potential requires fewer conditions like acquaintance or face-to-face interaction but depends more on the space organization. This article reports on a preliminary study of how Space Syntax as a quantitative approach is applied to the innovation-driven renovation in the case of South China University of Technology. The proposed method aims to sustain a sustainable transition towards a more adaptable relation between people and the campus environment. However, to improve understanding of innovation-driven renovation for university campuses, more empirical studies must be carried out.